Health Care Costs attributable to Hospital-diagnosed Back Pain: A Longitudinal Register-based Study of the Danish Population - Rikke Søgaard; Jan Sørensen (Journal of Health Economics and Outcomes Research)
**Background:** Back pain is one of most frequent musculoskeletal conditions with enormous impact to health care systems and society. Analytical studies that guide the management of this disease are strongly needed, but there is a lack of cost estimates for the attributable cost of severe or chronic back pain in particular.